Depositional Environment of the Late Miocene of Lemau Formation from Bengkulu Basin Based on Palynology in Seluma, Bengkulu, Indonesia - Mentari, Sakilla Gia; Winantris; Jurnaliah, Lia; Anjani, Novita Iwa (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Indonesia has several sedimentary basins, one of which is the Bengkulu Basin. One of the rock formations that make up this basin is the Lemau Formation, which is of Middle-Late Miocene age. Determining the depositional environment can use pollen and spore fossils stored in rocks. In the Lemau Formation, very little has been done to determine the depositional environment using pollen and spores. This research aims to reconstruct the sedimentary environment of the Lemau Formation rocks in the Late Miocene. Analysis was carried out on ten rock samples from Seluma, Bengkulu, Indonesia. Data collection used the stratigraphic measurements method, and laboratory analysis used the hydrogen peroxide method. There were five changes in the depositional environment, starting from the mangrove environment in sample BIL 21. The shallow environment became back mangrove in sample BIL 22, shallowing again became a peat swamp environment in samples BIL 23-BIL 26, the flooded environment became mangrove in sample BIL 27 and shallowing returned to a freshwater environment in samples BIL 28-BIL 30. Determination of the Late Miocene age used the presence of the Stenochlaenidites papuanus index fossil found in sample BIL 21. This environmental change was possible due to tectonic activities on the island of Sumatra in the Late Miocene and global eustatic changes.